2021
DOI: 10.3389/fpsyg.2020.624567
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Pandemic on University Students' Physical Activity Levels: An Early Systematic Review

Abstract: Purpose: This systematic review aimed to analyze the impact that the COVID-19 lockdown had on the amount of physical activity performed by university students.Materials and Methods: A systematic electronic search for studies providing information regarding physical activity levels pre and during COVID-19 pandemic in university students was performed up to 20th October 2020 in the databases Cochrane Library, PubMed, SPORTDiscus, and Web of Science. The risk of bias of external validity quality of included studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
152
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(221 citation statements)
references
References 49 publications
18
152
0
10
Order By: Relevance
“…Most of the countries extracted in this review are located in Europe and the Americas, where the number of infected people is considerable, and China, where the disease was first discovered and spread. Similar to the review of university students, 11 most studies were conducted in high- or upper-middle-income countries. As developing countries have limited medical resources and are facing vaccination delays, 35 , 36 a survey of the pandemic's impact on children is urgently needed even though the infection rate in such countries appears to be low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the countries extracted in this review are located in Europe and the Americas, where the number of infected people is considerable, and China, where the disease was first discovered and spread. Similar to the review of university students, 11 most studies were conducted in high- or upper-middle-income countries. As developing countries have limited medical resources and are facing vaccination delays, 35 , 36 a survey of the pandemic's impact on children is urgently needed even though the infection rate in such countries appears to be low.…”
Section: Discussionmentioning
confidence: 99%
“…López-Valenciano et al. 11 reviewed studies examining the PA of university students during the pandemic and found that nine out of ten reported a significant decrease in PA. They also noted that students who were sufficiently active before the pandemic remained sufficiently active during the confinements, despite reductions in their overall PA levels.…”
Section: Introductionmentioning
confidence: 99%
“…Increased stress with fear of contagion may prevent people from leaving home. On the other hand, imposed restrictions, closures of workplaces, recreation grounds, and forced social isolation are known to increase stress levels, for instance, as a result of deprivation of physical closeness (Stueck, 2021) or by limiting physical activity (López-Valenciano et al, 2021;Ruiz et al, 2021). With possible varying personality traits between residents of both countries (McCrae et al, 2005;Schmitt et al, 2007) and, consequently, different attitudes toward pandemic and lockdown policies (Schaller and Murray, 2008;Barceló, 2017), this may be one of the reasons behind perceived stress-level differences between the two discussed countries, although the actually imposed restrictions were similar in Poland and Italy at that time (Supplementary Tables 1, 2).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, physical inactivity could be one of the risk factors for BSC and QDC, as a lack of movement may affect our blood circulation. A recent systematic review found a significant reduction in physical activity levels among university students because of the COVID-19 pandemic [ 97 ]. The pandemic outbreak and the resulting lockdowns may have impacted university students’ ability to be physically active.…”
Section: Discussionmentioning
confidence: 99%